Molecular epidemiological characterization of Staphylococcus aureus isolates originating from food poisoning outbreaks that occurred in Tokyo, Japan. (October 2014) - Suzuki, Yasunori; Omoe, Katsuhiko; Hu, Dong‐Liang; Sato'o, Yusuke; Ono, Hisaya K.; Monma, Chie; Arai, Teruyoshi; Konishi, Noriko; Kato, Rei; Hirai, Akihiko; Nakama, Akiko; Kai, Akemi; et al.
Abstract Staphylococcal food poisoning (SFP), one of the commonest food‐borne diseases, results from the ingestion of one or more staphylococcal enterotoxins (SEs) produced in foods by Staphylococcus aureus. In the present study, 203 S. aureus strains originating from 83 outbreaks that had occurred in Tokyo were examined for their coagulase type and genotype of SEs to analyze their molecular epidemiological characteristics. The representative subsets of the 83 S. aureus isolates were analyzed by multilocus sequence typing (MLST) and S. aureus pathogenicity island (SaPI) scanning. The isolates were integrated into eight specific clonal complexes (CC) s; CC81, CC8, CC6, CC5, CC508, CC59, CC20 and CC30. The profiles of the coagulase type, SE/SEl genotype and the suspected type of enterotoxin‐encoding mobile genetic element (MGE) indicated a correlation with each CC. SaPI scanning showed fixed regularity between the distributions of genomic islands, including SaPIs, and the phylogenetic lineage based on MLST. These results indicate that the S. aureus isolates, which classified into eight CCs, have distinguishable properties concerning specific coagulase type, enterotoxin genotype and MGE type. Strains of S. aureus harboring these particular elements possess the potential to cause SFP.